Earth energy evolution, human development and carbon neutral strategy - Caineng ZOU; Feng MA; Songqi PAN; Minjie LIN; Guosheng ZHANG; Bo XIONG; Ying WANG; Yingbo LIANG; Zhi YANG (Petroleum Exploration and Development, 2022)
Energy is the basis of human development and the impetus of society progress. There are three sources of energy: energy of celestial body outside the Earth, the Earth energy and energy of interaction between the Earth and other celestial bodies. Meanwhile, there are three scales of co-evolution: the evolution of the Sun-Earth-Moon system on an ultra-long time scale has provided energy sources and extra-terrestrial environmental conditions for the formation of the Earth system; the evolution of the Earth system on a long time scale has provided the material preconditions such as energy resources and suitable sphere environment for life birth and the human development; on a short time scale, the development of human civilization makes the human circle break through the Earth system, expanding the extraterrestrial civilization. With the co-evolution, there are three processes in the carbon cycle: inorganic carbon cycle, short-term organic carbon cycle and long-term organic carbon cycle, which records human immoderate utilization of fossil energy and global sphere reforming activities, breaking the natural balance and closed-loop path of the carbon cycle of the Earth, causing the increase of greenhouse gases and global climate change, affecting human happiness and development. The energy transition is inevitable, and carbon neutrality must be realized. Building the green energy community is a fundamental measure to create the new energy system under carbon neutrality target. China is speeding up its energy revolution and developing a powerful energy nation. It is necessary to secure the cornerstone of the supply of fossil energy and forge a strong growing pole for green and sustainable development of new energy. China energy production and consumption structure will make a revolutionary transformation from the type of fossil energy domination to the type of new energy domination, depending on a high-level self-reliance of science and technology and a high-quality green energy system of cleaning, low-carbon, safety, efficiency and independence. Energy development has three major trends: low-carbon fossil energy, large-scale new energy and intelligent energy system, relying on the green innovation, contributing the green energy and constructing the green homeland.